Ethnographic Complexes as Catalysts for Regional Development: Insights from Chernihiv Region - Makeieva, Anastasiia (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Problem Statement. The reconstruction of public infrastructure destroyed by Russian aggression, along with the restoration of political, socio-economic, and cultural activity in the de-occupied territories, is an urgent need for the sustainable development of Ukraine's regions and local communities. In this context, tourism and excursion activities, particularly ethnographic tourism as their integral component, can and should become a powerful driver of local development. There is a pressing need for comprehensive research into the functioning of ethnographic tourism complexes under martial law, their financial and organizational potential as hubs of local entrepreneurship, preservation of historical and cultural heritage, enhancement of social cohesion, and post-war community development.The purpose of the article is to examine the role of ethnographic tourism complexes in the sustainable socio-economic development of territorial communities located in de-occupied regions of Ukraine.Research methods. To achieve this objective, the study applied a combination of qualitative and quantitative research methods: analysis and synthesis, statistical methods, case study and SWOT analysis.Results. The analysis revealed that “Sokolynyi Khutir” functions as a multifunctional tourism and cultural complex that combines ethnographic, museum, and entrepreneurial activities. The complex provides employment, supports local self-governance, fosters the cultural identity of the territorial community, and contributes to the preservation and promotion of both tangible and intangible cultural heritage. Its active involvement in social, charitable, and international initiatives strengthens social cohesion and enhances the tourist appeal of the destination. Between 2023 and 2024, the number of visitors increased, largely due to innovative approaches to cultural communication and digital promotion. The economic dimension of the complex’s activity is reflected in the growth of local budget revenues and the attraction of tourist and excursion flows, despite the challenging conditions of wartime.The novelty. This study presents the first comprehensive assessment of a privately owned ethnographic tourism complex operating under martial law from the standpoint of sustainable development criteria. The effectiveness of cultural and entrepreneurial practices in preserving national heritage and enhancing social stability within territorial communities is analyzed. The findings of the study can be used by local authorities, entrepreneurs, and researchers in developing strategies for the post-war recovery and development of de-occupied areas through the means of ethnographic tourism.